Challenges of regionalism: Development and spatial structure of the hungarian banking system section: Financial issues - Zoltán Gál (European Regional Science Association (ERSA), 2001)
The growing literature on regional finance suggests that credit allocation in regional banking system and the different national banking systems are different according to their stage of development, and frictions also exist across regions within national economies, resulting in different availability of capital. Less developed banking systems – including regional banks as well – have a lesser capacity to promote their economic development and might experience certain disadvantage as a result of the financial integration in Europe. Despite regional and local banks can serve local economic interests better than financial-centre banks whose priorities relate more to the single European and global markets, less advanced banking systems can be controlled more easily by the large universal banks of the financial core areas. This latter argument is refers very much to the accessing countries of Central and Eastern Europe, such as Poland, Czech Republic, Slovenia, Slovakia and Hungary which followed their reintegration into the world financial market in the early 1990s. They not only have to adopt new technologies and the financial behaviour it accommodates, but also have to cope with a legacy of bad debts and a lack of experience in credit risk assessment. Central –Eastern European banking systems are accelerating through some features of the stages of development as a result of competition with more advanced systems and state encouragement of banking development. As European Union membership approaches in Central Europe's more advanced economies, Western European banks are `aggressively' moving to expand into what will soon be a home market for them. The result is the increasing pressure on margins, as more banks compete for relatively little business. This results in a reversal process of concentration than in the EU, namely the growing number of institutions. Making matters worse for the locals, the foreign banks often boast deeper pockets, greater expertise and more solid reputation. All these challenges which are to be faced are common in these countries, but what could be varied from country to country is the spatial and institutional structure of the national banking systems. The paper is concerned with the spatial characteristics of the Hungarian banking system. Financial services became the key sector in the processes of economic transformation and differentiated by uneven regional development. The spatial structure of the banking sector is characterised by a large-scale concentration in Budapest, but the foundation boom of branch offices is also typical in the regions, as the necessity of presence on the local markets, as well as the competition for the retail market stimulate banks to expand their branch networks. Commercial banks, which have their headquarters exclusively in Budapest, largely concentrate only on the collections of deposits in their national network, resulting in capital drainage and net capital loss in most of the regions. The presence of the centralised capital market and the lack of decentralised regional financial system can restrain and slow down regional development in the long run. In this paper I would like to give an overview of the institutional and spatial structure and the development tendencies of the Hungarian banking which occurred during the first decade of two-tier banking. Allocation of branches of the banking institutions plays an important role, not only in the development of the national economy as a whole, but in the development of the local and regional economy, in innovation and, last but not least, in the organisation of production and service sectors. The elements of the banking network connect to regional development as the supply section of the business services therefore the density and the number of banks and their branches are an important indicator of regional economic development. The Hungarian banking system unlike its Polish counterpart is almost exclusively based on national branch-banking system, which means the lack of the regionally based independent universal banks. This very centralised structure of the national banking system and the growth of competition following the further liberalisation and decreasing barriers of the national market (e.g. cross-border banking and branching which primarily targeting corporate, but not the retail sector) might result to reduce credit availability for SMEs situated in the Hungarian regions remote from the capital city and from the European financial centres. In this respect, there may will be a case for creating regional banks in the forming regions of Hungary in order to protect local economy and facilitate to channel and mediate the EU regional development funds in the future. Larger countries in Europe (Germany, Poland, Italy etc.%29 show the rise of strong regional centres, based upon independent regional banks or decentralised back-office functions in certain provincial centres holding firm positions in large regional markets or based upon specialisation and complementarity. In contrast to this, the Hungarian banking exemplifies a pre-eminent position of the national financial centre partly due to Hungary's much smaller market size and the weakness of the regional economies. It seems plausible that there is no place for such strong regional financial centres in a small domestic market and the small geographical areas of the created regions, but to find the right way of certain decentralisation in the banking sector is inevitable. The paper is organised as follows. After the introductory section the spatial and structural characteristics and polarisation of the Hungarian banking system is discussed in the light of its progress made in the last ten years. This is followed by an analysis of a possible reorganisation and decentralisation (regionalisation) of the spatial structure of banking at regional level without questioning the pre-eminent role of the national banking centre, but contributing to a more efficient operation of the network. In the last instance, I will raise the question becomes whether the national banking system is ready to be fully liberalised and able to withstand increasing competition (with the introduction of the cross-border banking) within the European Union. This analysis rests on data, which are usually published with certain delay, coming from the Annual Report of the Bank and Capital Market Advisory Board, Regional Statistical Yearbook and from the Hungarian Almanac of Financial and Capital Markets. Most of these sources as well as publication in economics still neglect to consider geographical issues of the financial sector making more difficult the research efforts. From the geographical point of view, to survey the rapidly changing banking network in expansion phase make rather difficult to demonstrate accurate spatial structure of banking services.
Keywords: 330; Hungarian banking system; transitional financial markets; banking network; global-local dichotomy; and uneven regional development